Scientific And Practical Aspects of Providing Psychological Service in The Preschool Education System - Rajabova Muhayyo Yusupovna (Genius Journals, 2022)
Improving pre-school education, which is the first stage of education in the Republic of Uzbekistan, is one of the priorities of state policy. Radical reform of the pre-school education system in the country, creation of various forms of pre-school education organizations and providing them with highly qualified, modern-minded educators and specialists, high-quality improvement of pre-school education, Large-scale reforms aimed at the introduction of advanced foreign experience in the educational process are being carried out.
Keywords: psychological education; psychological services; psychological counseling; preschool education system